Hubungan Tingkat Pendidikan Ibu dengan Penanganan Demam pada Anak Di Wilayah Kerja Puskesmas Kronjo Tahun 2022 - Anggi Fibritiani; Mizwar Taufiq Pirmansyah; Widy Darmayanti; Emanuel Suban Bala Lewar; Juandri Seprianto Tusi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Fever is a sign or symptom of disease with an adaptive regulatory response of the body to stimuli in the immune system, autonomic system, behavior and neuroendocrine processes. Handling fever in children really depends on the role of parents, especially mothers. Mothers who know about fever and have a good attitude in providing care can determine the best fever management for their child. The aim of this study was to determine the relationship between maternal education level and the treatment of fever in children in the Kronjo Community Health Center Working Area. This research is an analytical survey research using a cross sectional design, the sampling technique in this research is nonprobability sampling. The results of the research show that there is a significant relationship between the level of maternal education and the treatment of fever in children in the Kronjo Health Center working area. These results were obtained based on the chi square test, with a value of p = 0.007 < 0.05. Maternal education has been proven to influence the treatment of fever in children, so mothers need to be aware of the treatment of fever in children in order to provide appropriate treatment for fever in children.